فاعلية الإدارة الإسلامية في تحسين الأداء الوظيفي من خلال تمكين الموظفين في مراكز خدمات إسعاد المتعاملين بإمارة أبو ظبي: The Effectiveness of Islamic Management in Enhancing Job Performance through Employee Empowerment at Customer Happiness Centers in Abu Dhabi - Balhai Khair Alkuwaiti, Balhai Khair (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
ملخص البحث تهدف هذه الدراسة إلى تحليل أثر الإدارة الإسلامية في تعزيز الأداء الوظيفي من خلال تمكين الموظفين في مراكز خدمات إسعاد المتعاملين في أبو ظبي. تنطلق الدراسة من إدراك أهمية الأداء الوظيفي بوصفه من أهم العوامل نجاح المؤسسة والمعيار الحقيقي لقياس كفاءة العنصر البشري. برزت المشكلة، بوجود تحديات تؤثر على أداء مراكز المتعاملين منها؛ إدارة حجم الطلب وزيادة القدرة الاستيعابية، تعدد المنصات الرقمية غير المترابطة لدوائر مختلفة. نقص تدريب وتأهيل العاملين، عدم إشراك المتعاملين في تصميم الخدمات، مما تسبب في بطء أداء المراكز. للتحقق من المشكلة أجرى الباحث دراسة استكشافية، شملت مقابلات، أكدت تلك المشكلات بسبب ضعف تعليم الأجيال السابقة، تفكك روابط بعض الأسر وتخلي البعض عن الآباء. هدفت الدراسة: قياس أثر الإدارة الإسلامية في زيادة الأداء الوظيفي، وتمكين الموظفين. ومدى قيام المتغير الوسيط بدور الوساطة بين المتغير المستقل والتابع. بلغ حجم مجتمع الدراسة (3340) مديراً وموظفاً إدارياً، أختيرتْ عينة طبقية (346) حسب جدول جريستي ومورغان، وباستخدام المعادلة. طور الباحث مقياسين للدراسة بالاستفادة من الأدبيات السابقة، الأول للموظفين: تكون من (70) عبارة موزعة في (3) محاور شملت (14) بعدا. الثاني للمتعاملين: من (16) عبارة موزعة في (4) أبعاد. تم التحقق من صدق المحكمين، وصدق المحتوى، وصدق الاتساق الداخلي، تحليل التباين لتحقيق الفرضيات. كما بينت النتائج أن الإدارة الإسلامية تؤثر إيجابيًا وبصورة جوهرية على تحسين الأداء الوظيفي، إ ذ تمثل الأداة التنفيذية التي تحول الخطط الاستراتيجية إلى ممارسات تنظيمية فعّالة من خلال استقطاب الكفاءات وتطويرها وتحفيزها. كذلك أثبتت النتائج أن الإدارة الإسلامية تلعب دورًا وسيطًا بين الأداء الوظيفي وتمكين الموظفين، مما يعني أن أثر الإدارة الإسلامية على الأداء الوظيفي يمر بدرجة كبيرة عبر تمكين الموظفين. وهذا يؤكد أهمية تكامل الإدارة الإسلامية مع سياسات تنمية تمكين الموظفين لضمان استدامة التميز المؤسسي. خلصت الدراسة إلى أن تعزيز الأداء الوظيفي في مراكز المتعاملين يتطلب تكاملًا بين التخطيط الاستراتيجي المرن وإدارة المواهب الفعالة، بما يحقق القدرة على الابتكار والتكيف مع المتغيرات البيئية. وأوصت بضرورة ترسيخ ممارسات التخطيط الاستراتيجي القائمة على البيانات والتحليل المستقبلي، وتطوير سياسات ممنهجة لاكتشاف الكفاءات وتنميتها بما يتوافق مع أولويات مراكز المتعاملين أبو ظبي وأهدافها الاستراتيجية. تُسهم هذه الدراسة في إثراء الأدبيات الإدارية العربية حول الإدارة الإسلامية والأداء الوظيفي في مراكز المتعاملين، وتقدم نموذجًا تطبيقيًا يمكن الاستفادة منه في تطوير الممارسات الإدارية الحديثة في القطاع العام، بما يعزز الكفاءة والابتكار والاستدامة المؤسسية في بيئة العمل الحكومي. ABSTRACT This study aims to analyze the impact of Islamic management on enhancing job performance through employee empowerment at customer happiness centers in Abu Dhabi. The study stems from the recognition of the importance of job performance as a key factor in organizational success and a true measure of human resource efficiency. The problem of research lies on challenges affecting customer center performance, including: managing demand and increasing capacity; the proliferation of unconnected digital platforms across different departments; inadequate employee training and development; and the lack of customer involvement in service design, all of which contributed to slow center performance. To investigate the problem, the researcher conducted an exploratory study, including interviews, which confirmed these issues, attributing them to the limited education of previous generations, the breakdown of family ties, and parental neglect. The study aimed to: measure the impact of Islamic management on increasing job performance and employee empowerment; and assess the extent to which the mediating variable acts as an intermediary between the independent and dependent variables. The study population consisted of 3,340 managers and administrative staff. A stratified sample of 346 was selected using the Griskie and Morgan scale and the formula. The researcher developed two scales for the study, drawing on previous literature. The first scale, for employees, consisted of 70 statements distributed across three axes encompassing 14 dimensions. The second scale, for customers, consisted of 16 statements distributed across four dimensions. The validity of the experts, content validity, and internal consistency were verified, and analysis of variance was performed to test the hypotheses. The results showed that Islamic management has a significant and positive impact on improving job performance. It serves as the executive tool that transforms strategic plans into effective organizational practices by attracting, developing, and motivating talent. Furthermore, the results demonstrated that Islamic management plays a mediating role between job performance and employee empowerment, meaning that the impact of Islamic management on job performance is largely mediated through employee empowerment. This underscores the importance of integrating Islamic management with employee empowerment development policies to ensure the sustainability of organizational excellence. The study concluded that enhancing employee performance in customer service centers requires an integration of flexible strategic planning and effective talent management, enabling innovation and adaptation to environmental changes. It recommended establishing data-driven strategic planning practices based on future analysis and developing systematic policies for identifying and developing competencies in line with the priorities and strategic objectives of Abu Dhabi’s customer service centers. This study contributes to enriching Arabic administrative literature on Islamic management and employee performance in customer service centers, and offers a practical model that can be used to develop modern administrative practices in the public sector, thereby enhancing efficiency, innovation, and institutional sustainability in the government work environment.